2018
DOI: 10.1002/macp.201800371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blend Composition on Scratch Behavior of Polystyrene/Poly(2,6‐dimethyl‐1,4‐phenyleneoxide) Blends

Abstract: The relationship between the scratch behavior and molecular aggregation states of polystyrene (PS), poly(2,6‐dimethyl‐1,4‐phenyleneoxide) (PPO), and their blends, is investigated based on differential scanning calorimetry (DSC), wide‐angle X‐ray diffraction (WAXD), polarized optical microscopy (POM), and indentation and scratch tests. DSC reveals that all the PS/PPO blends show the single glass transition temperature (Tg) and the Tg monotonically increase and Tg breadth exhibits a maximum, with an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…[ 1–8 ] Thus, to overcome these defects and add new properties, several studies have modified the PPE in various ways such as polymer blending with polystyrene (PS), nylon‐66 (PA‐66), nylon‐6 (PA‐6), polyethylene octene (POE), polybutylene terephthalate (PBT), or manufacturing high‐performance PPE alloy to improve the toughness of alloy material. [ 9–19 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1–8 ] Thus, to overcome these defects and add new properties, several studies have modified the PPE in various ways such as polymer blending with polystyrene (PS), nylon‐66 (PA‐66), nylon‐6 (PA‐6), polyethylene octene (POE), polybutylene terephthalate (PBT), or manufacturing high‐performance PPE alloy to improve the toughness of alloy material. [ 9–19 ]…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Thus, to overcome these defects and add new properties, several studies have modified the PPE in various ways such as polymer blending with polystyrene (PS), nylon-66 (PA-66), nylon-6 (PA-6), polyethylene octene (POE), polybutylene terephthalate (PBT), or manufacturing high-performance PPE alloy to improve the toughness of alloy material. [9][10][11][12][13][14][15][16][17][18][19] Among various types of PPE alloys, PPE/PS alloy was first commercialized and played an important role in the history of polymer blends. The PPE and PS of lower melt viscosity are completely compatible systems that can be blended in any ratio to significantly improve the melt flow of PPE resin.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous dewetting experiments using a combination of polymers focused on double layers of two immiscible polymers. Only a few studies were based on blends of miscible or partially miscible polymers. ,, Müller-Buschbaum et al , observed that blends of deuterated atactic polystyrene (dPS) and atactic poly­( para -methylstyrene) (aP p MS) were unstable. One component had an affinity for the substrate interface (dPS) and the other for the air interface (aP p MS), favoring phase separation into two layers.…”
Section: Introductionmentioning
confidence: 99%